Characteristics and generation mechanisms of anticyclonic eddies, cyclonic eddies and dipole eddies in the Mozambique Channel - Huang, Ting; Zhou, Feng; Ma, Xiao; Zeng, Dingyong; Tang, Yong; Ma, Yunlong; Raul, Andre Emidio; Ding, Ruibin; Mafuca, Jorge Mario; Ye, Ruijie; Huang, Daji (Frontiers in Marine Science, 2024)
The discovery of cyclonic and dipole eddies in the Mozambique Channel (MC) indicates that the understanding of the mesoscale eddy characteristics in the MC is incomplete. The distributions of anticyclonic, cyclonic, and dipole eddies along the MC were elucidated in this study using satellite observations. It was observed that these eddies exhibit a preference for emergence and movement in the western MC. The occurrence frequencies of anticyclonic and cyclonic eddies are four and three times per year, respectively, in the narrowest section of the MC. In contrast, the frequency of mesoscale eddies reaches its peak at nine times per year in the central region of the MC. The occurrence of dipole eddies also reaches its peak twice per year in the middle MC. Dipole eddies are more prevalent in the MC and exhibit larger dimensions and shorter lifespans compared to anticyclonic and cyclonic eddies. Mesoscale eddies, which traverse the narrowest section of the MC and propagate southward, are predominantly generated within the western Comoros Basin due to barotropic instability. The southward branch of the Northeast Madagascar Current (NEMC) plays a crucial role in transporting these eddies to the middle MC. The eastern middle MC is also a generation site for mesoscale eddies in addition to the Comoros Basin, where cyclonic eddies are generated twice per year. These cyclonic eddies are also generated due to barotropic instability.